1991
DOI: 10.1099/00221287-137-3-615
|View full text |Cite
|
Sign up to set email alerts
|

Chitin synthesis in Fusarium graminearum and its inhibition by edifenphos (Hinosan)

Abstract: Membrane-bound chitin synthase from FuscUium graminearum A315 had a pH optimum of 6.5, an apparent temperature optimum of 30 "C and an apparent K,,, for UDP-N-acetylglucosamine (UDP-GlcNAc) of 2.5 mM.Digitonin-solubilized chitin synthase had a lower (about 25% of the original activity) and more variable activity than the membrane-bound chitin synthase from which it was prepared. The activity of solubilized chitin synthase was stabilized by incorporating Allosamidin (a chitinase inhibitor) into the reaction mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It has been reported that PC biosynthesis is inhibited by edifenphos and iprobenfos (Kodama et al, 1979(Kodama et al, , 1980Binks et al, 1990), and we have demonstrated that reduced levels of PC in a choline-requiring strain of Aspergillus nidulans (choA) were correlated with reductions in (a) the rate of in vivo chitin synthase, (b) colony radial growth rate, and (c) hyphal growth unit length . When the effects of edifenphos on F. graminearum, B. fabae and P. oryzae were examined, PC levels were found to be reduced but at markedly different fungicide concentrations (Table 1) this respect, P. oryzae was the most sensitive edifenphos followed by B. fabae with F. graminearum least sensitive, suggesting that the sensitivities of colony radial growth rates of the three fungi edifenphos may be due to a differential sensitivity inhibition of PC biosynthesis.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…It has been reported that PC biosynthesis is inhibited by edifenphos and iprobenfos (Kodama et al, 1979(Kodama et al, , 1980Binks et al, 1990), and we have demonstrated that reduced levels of PC in a choline-requiring strain of Aspergillus nidulans (choA) were correlated with reductions in (a) the rate of in vivo chitin synthase, (b) colony radial growth rate, and (c) hyphal growth unit length . When the effects of edifenphos on F. graminearum, B. fabae and P. oryzae were examined, PC levels were found to be reduced but at markedly different fungicide concentrations (Table 1) this respect, P. oryzae was the most sensitive edifenphos followed by B. fabae with F. graminearum least sensitive, suggesting that the sensitivities of colony radial growth rates of the three fungi edifenphos may be due to a differential sensitivity inhibition of PC biosynthesis.…”
Section: Discussionmentioning
confidence: 83%
“…In F. graminearurn, we have previously shown that inhibition in colony radial growth rate by edifenphos is initially due to direct non-competitive inhibition of chitin synthase with no reduction in PC; only at edifenphos concentrations of about 250 p~ and above is a reduction in PC observed with additional inhibition of chitin synthase (Binks et al, 1990, Table 1). In the moderately sensitive fungus B. fabae, reductions in colony radial growth rate appear to be due to a combination of both direct inhibition of chitin synthase activity and an indirect inhibition of this enzyme due to a reduction in the PC content of the membrane ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, the agricultural fungicide edifenphos, which is known to affect membrane phospholipid composition, was found to cause noncompetitive inhibition of chitin synthetase from Fusarium graminearum within specific concentration ranges (21).…”
Section: Compounds Active Against Fungal Cell Walls Inhibitors Of Chimentioning
confidence: 99%